Effects of supplementing with an 18% carbohydrate-hydrogel drink versus a placebo during whole-body exercise in -5°C with elite cross-country ski athletes: a crossover study - Pettersson, S.; Edin, F.; Bakkman, L.; McGawley, K. (Journal of the International Society of Sports Nutrition, 2019)
Whilst the ergogenic effects of carbohydrate intake during prolonged exercise are well-documented, few investigations have studied the effects of carbohydrate ingestion during cross-country skiing, a mode of exercise that presents unique metabolic demands on athletes due to the combined use of large upper- and lower-body muscle masses. Moreover, no previous studies have investigated exogenous carbohydrate oxidation rates during cross-country skiing. The current study investigated the effects of a 13C-enriched 18% multiple-transportable carbohydrate solution (1:0.8 maltodextrin:fructose) with additional gelling polysaccharides (CHO-HG) on substrate utilization and gastrointestinal symptoms during prolonged cross-country skiing exercise in the cold, and subsequent double-poling time-trial performance in ~ 20°C.